Challenges in Building Robust Interventions in Contexts of Poverty: Insights from an NGO-driven multi-stakeholder network in Ethiopia. Issue 10 (October 2020) - van Wijk, Jakomijn; van Wijk, Jeroen; Drost, Sarah; Stam, Wouter
We examine the demise of a multi-stakeholder network that was launched to promote an inclusive dairy market in Ethiopia to better understand why nongovernmental organizations (NGOs) may develop interventions in contexts of poverty that fail to endure after they exit. We identify organizational reflexivity – the capacity to recognize and understand the recursive interplay between an intervention and the local environment – as a key explanatory mechanism for this intervention outcome. Limited reflexivity not only prevented the NGO we studied from properly aligning the intervention with the context ( design failures ), but also prevented the organization from adjusting its intervention when negative feedback emerged ( orchestration failures ), which eventually evolved into the demise of the network ( maintenance failure ). While our study confirms the theoretical premise that NGOs need to contextualize their interventions, we expand current knowledge by highlighting the role of organizational reflexivity in this process. Moreover, by showing how reflexivity deficits can trigger a cascade of failure, especially when intervening in voids where incumbent firms have interests in maintaining the void, our study calls attention to the politicized nature of institutional voids.